Era preciso cola para unir os cacos - Flores, Michel Machado (2018)
This dissertation proposes a reading about Opisanie świata, a book by the Brazilian writer Veronica Stigger, using theories of art and literature. In its first part, I deal with the displacement of words and images from other forms and sources into the interior of a fictional narrative. In this part, the displacement is seen as an operation of artistic and literary creation, capable of overcoming these and other barriers. For this, I use texts of the author herself and critics that elucidate this gesture in the works of Marcel Duchamp, Kurt Schwitters and Veronica Stigger. Then, in the second part of this work, I turn to a story from the narrative, derived from the thought of Walter Benjamin, to think of it from the various forms of narration that are experimented by Stigger in her prose. In this way, it worthy nothing that all the displacements observed in this narrative and the different forms of narration experienced by the writer are seen, in the company of works by other narrators, as pieces assembled in a collage. Finally, the last chapter presents a conversation with the author in which I look for information that deals with her work as a whole and that corroborates the discussion presented in the previous chapters.